Research Progress on the Association Between Heart Rate Variability Based on the Theory of "Heart Governing Spirit" and Ischemic Brain White Matter Hyperintensity with Mild Cognitive Impairment - Zhao, Yuanjiang; Zhang, Xiaole (Journal of Contemporary Medical Practice, 2026)
With the acceleration of population aging, dementia has become a major global public health crisis. Vascular dementia (VD) is one of the most prevalent dementia subtypes, and the identification and intervention of its prodromal stage—mild cognitive impairment (MCI)—are of great clinical significance. Heart rate variability (HRV), the gold standard non-invasive biomarker for evaluating cardiac autonomic nervous function, has been proven to be closely correlated with cognitive function in recent studies. Ischemic white matter hyperintensities (WMH) represent the core imaging manifestation of cerebral small vessel disease, and serve as an important early marker of vascular cognitive impairment. Patients co-occurring with WMH and MHI carry a high risk of progression to dementia. Based on the traditional Chinese medicine (TCM) theory of “the heart governing the spirit”, this paper systematically reviews the physiological basis of HRV and clinical research progress of WMH combined with MCI, deeply explores the potential mechanisms linking HRV and WMH-related cognitive impairment, analyzes the clinical value of HRV as an early warning biomarker for this patient population, and proposes future research directions in response to existing research limitations. This review proposes that HRV can act as a quantitative objective indicator for the theory of “the heart governing the spirit”, providing a non-invasive, dynamic early warning tool for the highly heterogeneous population with WMH complicated by MCI, and offering novel research ideas for integrated traditional Chinese and Western medicine prevention and treatment of cognitive disorders.